El reclutamiento militar en España a comienzos del siglo xvii (1600-1625): problemas y soluciones - Antonio José Rodríguez Hernández; Manuel Díaz-Ordóñez (Mélanges de la Casa de Velázquez, 2020)
This essay offers a general analysis of how worked the administrative system of recruitment used by the Spanish monarchy at the beginning of the 17th century. On the one hand, we approach the key lines of how the process, the instructions, or the districts of recruitment were organized. On the other hand, we analyze the principal problems of the system already mentioned by the historiography, and the solutions implemented by the Council of War to remedy the situation. Specially studying the social problems and of public order generated by the troops during the enrollment, and the elements of control, like the commissioners. In this system, the main burden of the recruitment was in the hands of the captains. To know their real professional skills is necessary to go in depth into the systems of captains’ appointments, the quality and experience of the applicants, or the importance of the venality, which is also developed in this text.